(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Effective environmental management in urban areas is increasingly vital, as more than half of the global population - 4.6 billion people, now resides in cities. Ensuring the socio-economic integration and well-being of urban populations requires not only addressing environmental challenges but also fostering inclusive and resilient urban development. Urban areas are particularly vulnerable to the impacts of climate change, necessitating proactive and adaptive approaches to problem identification and resolution. The concepts of Good Environmental Governance, Urban Green Infrastructure (UGI), and Nature-based Solutions (NbS) offer comprehensive frameworks for planning urban green spaces. These approaches emphasize the dual need to ground urban planning in scientific principles that promote healthy and vibrant cities, while also addressing the needs and interests of all stakeholders, including biodiversity. Participation plays a central role in designing and implementing green and climate-resilient urban environments. This article examines the role of public participation as a key indicator of effective urban greening, using the city of Yerevan as a case study. We analyzed relevant environmental management documents, including the Yerevan Climate Adaptation Plan and the Greening and Improvement Program, through the lens of innovative governance. To assess participation levels, we conducted stakeholder mapping - focusing particularly on those involved in greening initiatives, and carried out interviews with key stakeholders. The analysis adopts a bottom-up perspective to evaluate strategic planning documents and highlights areas where participatory approaches could be strengthened for more effective environmental governance. The stakeholder engagement model proposed in this study is applicable at both community and strategic planning levels and can inform broader policy development processes.